2009
DOI: 10.29333/ejgm/82647
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Virus (HCV) in Relation to Its Promotive Factors among Human Urban Population of Multan, Pakistan

Abstract: Aim:The present study was carried out to assess the prevalence of hepatitis C virus (HCV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…A detailed study of our results shows that the maximum number of people infected with HCV fall in the age groups between 26 to 55 years in district Swat. These results show similarities to the study of Ali et al [24], Shah et al [11] on the prevalence HCV. But also disagrees to the study that records high HCV occurrence among the younger or older age groups [25].…”
Section: Discussionsupporting
confidence: 91%
“…A detailed study of our results shows that the maximum number of people infected with HCV fall in the age groups between 26 to 55 years in district Swat. These results show similarities to the study of Ali et al [24], Shah et al [11] on the prevalence HCV. But also disagrees to the study that records high HCV occurrence among the younger or older age groups [25].…”
Section: Discussionsupporting
confidence: 91%
“…Along with this, the unclean dental equipment is common in almost every dental clinic of Pakistan (Ali et al, 2009a). In our study, it was found that most of the people infected with hepatitis C were health care workers because they have a higher risk of getting hepatitis C virus through contact with the blood and blood products of the patients.…”
Section: Discussionmentioning
confidence: 80%
“…Infectious diseases including Hepatitis C are major health issues in various developing countries including Pakistan (Ali et al, 2009a;Khan and Siddiqui, 2007). According to an estimate of the World Health Organization, hepatitis C has effected almost 3% population of the world, an estimate of 170 million people, with an increase in three to four million new cases every year (Raza et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible routes of transmission of HCV genotypes among the subjects. 21,22 The reason could be prognosis of HCV and awareness of health department of the region to aware them. Current study observed that untypable genotypes was the most predominant (43.5%), followed by 3a (29.6%) 3 b (9.6%), 2a (5.93%), 1a (5.3%), 1 b (4.0%), and 2 b (1.9%) genotype in district Buner population (table.No2) as noticed in the available literature when compiled showed that HCV genotype 3a (58.16%) was predominant in Pakistan, followed by 3 b (9.05%), 2a (6.70%), 1a (6.22%), and 1 b (2.39%), the findings of the study disagreed to our findings.…”
Section: Tablementioning
confidence: 99%